2002
DOI: 10.1021/jf0113427
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Whey Fermentation Using Kefir Yeast Immobilized on Delignified Cellulosic Material

Abstract: Delignified cellulosic-supported biocatalyst, prepared by immobilization of kefir yeast on delignified cellulosic material (DCM), was found to be suitable for continuous, modified whey fermentation. The modified whey contained 1% raisin extract and molasses. Ethanol productivities ranged from 3.6 to 8.3 g L(-1)day(-1), whereas parameters such as ethanol concentration, residual sugars, and daily fermented whey productivity were acceptable for the production of potable alcohol and alcoholic drinks in industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 18 publications
2
23
0
6
Order By: Relevance
“…10 Ethanol production from cheese whey has been investigated by many groups. [11][12][13][14][15][16][17][18][19][20][21] In some countries (New Zealand, the United States, and Denmark) bioethanol is produced from whey. 9,22 Due to the low lactose content of whey, however, its fermentation yields only about 2-3% (v/v) ethanol; this makes this process unfeasible at an industrial level, because of the costs of distillation.…”
Section: Introductionmentioning
confidence: 99%
“…10 Ethanol production from cheese whey has been investigated by many groups. [11][12][13][14][15][16][17][18][19][20][21] In some countries (New Zealand, the United States, and Denmark) bioethanol is produced from whey. 9,22 Due to the low lactose content of whey, however, its fermentation yields only about 2-3% (v/v) ethanol; this makes this process unfeasible at an industrial level, because of the costs of distillation.…”
Section: Introductionmentioning
confidence: 99%
“…Other meat products include mold-ripened hams, for example " Bündnerfleisch" from Switzerland, " Südtiroler Bauernspeck" from Tirol, and Italian "coppa" [2]. A mixed culture consisting of a variety of species of the genera Kluyveromyces, Candida, Pichia, and Saccharomyces and some lactic acid bacteria can be used to produce Kefir by fermenting milk whey or fruit juice [24].…”
Section: Raw Materials Product And/or Process Predominant Yeast or Funmentioning
confidence: 99%
“…Kourkoutas et al [10] proposed a low-alcohol content drink by using continuous whey fermentation, using kefir yeast. It was reported that kefir was highly resistant to contamination under actual industrial conditions and no serious problems in handling of raw materials and equipment were observed [11].…”
Section: Introductionmentioning
confidence: 99%